Community Satisfaction with Online Services in East Lombok Regency: (Case Study: BAKSO Application) - Ahdarrijal, Yujitia; Pribadi, Ulung (Scientific Journal of Informatics, 2024)
Purpose: This study analyzes the use of the BAKSO (Create Online Population Administration) application for users, namely employees of the East Lombok Regency Population and Civil Registration Office and the Admin of each village. The measurement uses variables consisting of infrastructure, ICT, bureaucracy, leadership, and implementation of digital government.Methods: The method used is a quantitative type, primary data in the form of a survey of 115 respondents from East Lombok Regency Population and Civil Registration Office office employees and village admins who used the BAKSO application (Create Online Population Administration). Using the Likert Scale (1: strongly disagree, 2: disagree, 3: neutral, 4: agree, and 5: strongly agree). The analysis technique for this study uses SmartPLS 3.Results: The results of this study show that infrastructure and ICT variables have a positive and significant influence on the implementation of digital government in the implementation of the BAKSO application. Meanwhile, bureaucratic and leadership variables have little impact and are substantial in implementing the BAKSO application in East Lombok Regency.Novelty: This study is unique because it examines users who are also employees who use the BAKSO application (Make Online Population Administration) with a measuring indicator, namely the online service index (OSI); most of the previous research on this theory was only oriented to assessing public satisfaction with online services. This research provides a new perspective on using the Online Service Index (OSI) on the scope of application-based online services from an employee perspective. In addition, the empirical contribution lies in the professionalism of employees in using the BAKSO application. So that later, it can provide space for the government to pay attention to human resources in running Online Service Index (OSI)-based application services.